Spectrofluorimetric Determination of Arsenic(III) in Water Samples - Zhu, R.H.; Chen, L.H. (Asian Journal of Chemistry, 2011)
A novel analytical method for determination of trace arsenic(III) is established by kinetic spectrofluorimetric. The method is based on quenching of the fluorescence, Rhodamine B, by the action of iodine, which is released by the reaction between arsenic(III) and potassium iodate in acidic medium. Under the optimized conditions, the detection limit was 0.5 μg L-1, the relative standard deviation was 3.2 % for arsenic(III) (c = 40 μg L-1, n = 6). The recovery of real arsenic(III) samples were in the range of 95.6-104.1 %. This method has been applied for the trace of arsenic(III) detection in real water samples. The results indicated that there was a good linearity between the fluorescence intensity of Rhodamine B and the concentration of arsenic(III).